Impact of Marketing 4.0 on Customer Engagement and Customer Satisfaction (International Journal of Food and Nutritional Sciences, 2022)
This research paper investigates the impact of Marketing 4.0 strategies and practices on customer engagement and satisfaction. The study adopts a quantitative approach, collecting data through a structured questionnaire from a diverse sample of 210 participants. The objectives of the study were to examine the influence of Marketing 4.0 on customer engagement and assess its effects on customer satisfaction. The findings reveal that the implementation of Marketing 4.0 strategies, including personalized experiences, co-creation, and interactive engagements, significantly enhances customer engagement levels. Moreover, the adoption of Marketing 4.0 practices, such as providing tailored offerings, convenient experiences, and efficient communication channels, leads to increased customer satisfaction. These findings highlight the importance of embracing Marketing 4.0 in fostering active customer participation, creating a sense of community, and delivering personalized experiences to enhance engagement and satisfaction.